Political discourse, military and securitization of health nexus: contemporary security challenges and the military role in public health security - Vanja Rokvić; Vladimir Ajzenhamer (Srpska Politička Misao)
The purpose of this paper is to provide answers to the questions why health is viewed through the lens of national and international security, and what might be the potential role of the armed forces in strategic response to health security challenges. Relying on theoretical settings of Foucault’s discourse studies and securitization concept developed by the Copenhagen School of security studies, authors will try to illuminate the nexus between political discourse, military and securitization of health. The analysis of the political and academic discourse has found that with regard to security the most important health challenges are considered the occurrence and spread of infectious diseases, especially HIV/AIDS, and the ability to make use of biological agents as weapons. As the most important reasons why health is viewed through the lens of security are considered to be major economic losses incurred due to health crises, high mortality rates, migration, the impact of health crises on the armed forces and peacekeeping operations. The paper concluded that the armed forces play a role in the public health security through monitoring and early warning, through epidemiological and laboratory opportunities for early detection of new epidemics or pathogens, as well as through providing assistance after major natural disasters. The paper analyzes the public health and security in the Republic of Serbia, and it was concluded that it is necessary to undertake more efforts in recognizing health as a field of national security, and health risks as the risks of security.